2012
DOI: 10.1155/2012/876028
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Mathematics: Effects of Individual, Motivational, and Social Support Factors

Abstract: This paper aims to understand how certain different but interrelated variables such as background, motivation, and social support could lead to an explanation of student attitudes towards math and to an understanding of the defining characteristics of these attitudes in the school environment. Participants consisted of 1719 Portuguese students, from fifth-to-twelfth grade. The study utilizes an adaptation of the “Intrinsic Motivation Inventory” assessing main determinants of intrinsic motivation. One section o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
133
1
17

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(196 citation statements)
references
References 37 publications
17
133
1
17
Order By: Relevance
“…According Eshun and Zan, Mata, Monteiro, & Peixoto (2012), negative attitudes associated with negative emotional disposition. The disposition of these emotions have an impact on student behavior consider the useful of mathematics, and do not enjoy math.…”
Section: Attitudes Towards Mathematicsmentioning
confidence: 99%
“…According Eshun and Zan, Mata, Monteiro, & Peixoto (2012), negative attitudes associated with negative emotional disposition. The disposition of these emotions have an impact on student behavior consider the useful of mathematics, and do not enjoy math.…”
Section: Attitudes Towards Mathematicsmentioning
confidence: 99%
“…Researchers (Attard, 2012;Grootenboer et al, 2008;Mata, Monteiro, & Peixoto, 2012) have identified important factors that contribute to students' attitudes towards learning mathematics. These include the students themselves, the school, the teachers' beliefs and attitudes (Beswick, 2006) and their teaching methods.…”
Section: Students' Attitudes Towards Learning Mathematicsmentioning
confidence: 99%
“…Attitudes are deeply related to motivation and social support. It is believed that developing strategies in educational contexts, to improve teacher support and student engagement could be of vital importance in improving not only attitudes but also mathematical performance among students throughout their schooling [4].…”
Section: Type Of School Graduatedmentioning
confidence: 99%
“…4. Students with higher and positive attitudes and beliefs towards mathematics performed better than students with lower attitudes and beliefs.…”
mentioning
confidence: 94%